Bewoningstevredenheid onder inwoners van hoë- en mediumdigtheidsbehuising in Groter Bloemfontein - Campbell, Malene; Lazenby, Kobus (Acta Structilia, 1998)
In order to evaluate urban facilities and services according to the needs identified by the residents of the Greater Bloemfontein certain determinants of residential satisfaction in the Greater Bloemfontein were investigated. The evaluation was also carried out to establish guidelines in the first place and secondly to identify the role of the community and policy formulators as well as role-players in the private sector (developers, builders, town-planners and architects) to attain a higher level of residential satisfaction under residents. *This article is written in Afrikaans.